Mengoptimalkan Customer Relationship Management untuk Menarik Kolaborator dengan Penggunaan Digital Marketing pada Perusahaan Kasihinbaju.Id - Nashah, Dar'el; Satyanegara, Diqbal; Putri, Solehatin Ika (Universitas Sultan Ageng Tirtayasa, 2024)
The article aims to determine the optimizing of Customer Relationship Management (CRM) using digital marketing on Kasihinbaju.id. Descriptive methods are used to describe the implementation of Customer Relationship Management (CRM) stages through digital marketing on Kasihinbaju.id. The result is that three stages in implementing the Customer Relationship Management stages, namely getting or attracting new customers (Acquire), improving relationships with existing customers (Enchance), and finally retaining existing customers (Retain Cost). Apart form the tree stages in optimizing the implementation of the Customer Relationship Management stages, Kasihinbaju.id uses 2 forms of CRM, namely Operational CRM and Collaborative CRM. The application and form of CRM aims to achieve success in attracting customers and this success can be seen by achieving sales targets.